Influence of milling time on mechanically assisted synthesis of Pb0.91Ca0.1TiO3 powders - Siqueira, J. R. R.; Simoes, A. Z.; Stojanovic, B. D.; Paiva-Santos, C. O.; Santos, L. P. S.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2007)
Pb0.91Ca0.1TiO3 powders (PCT) were prepared by mechanochemical synthesis from high-energy ball milling process. The influence of milling time on the phase formation, crystal structure, specific surface area, density and powder morphology was observed. We adopted the Rietveld refinement technique to investigate the crystal structure of the PCT powders. Scanning electron microscopy (SEM) analysis revealed that PCT powders milled for 5 h showed a wide distribution of particle agglomerates while milled for 35 h showed a decrease in agglomerates size. Further prolongation of milling time resulted in the agglomerates growth. (C) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: milling; X-ray methods; perovskites